Development of Spider using JAVA for broken links checking / Mahfudzah Ishak - Ishak, Mahfudzah (2009)
This thesis describes the implementation of Spider program using JAVA programming language for broken links checking. The main objective of the research is to develop a Spider program to check broken links on the websites using JAVA. Java is a particularly good choice as a language to construct a spider. Java has built-in support for the HTTP protocol, which is used to transfer most Web information. Java also has an HTML parser built in. Both of these two features make Java an ideal choice for spiders. Besides, this Spider program provides a proper arrangement of result from the Spider program to make it easy to read by users.